2022
DOI: 10.3390/nu14020340
|View full text |Cite
|
Sign up to set email alerts
|

Hydroethanolic Extract of Prunus domestica L.: Metabolite Profiling and In Vitro Modulation of Molecular Mechanisms Associated to Cardiometabolic Diseases

Abstract: High consumption of fruit and vegetables has an inverse association with cardiometabolic risk factors. This study aimed to chemically characterize the hydroethanolic extract of P. domestica subsp. syriaca fruit pulp and evaluate its inhibitory activity against metabolic enzymes and production of proinflammatory mediators. Ultra-high-performance liquid chromatography high-resolution mass spectrometry(UHPLC-HRMS) analysis showed the presence of hydroxycinnamic acids, flavanols, and glycoside flavonols, while nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 66 publications
(81 reference statements)
3
14
0
Order By: Relevance
“…The higher TSC of the fruits collected in 2021 could be explained by the maturity stage and/or annual weather conditions [ 6 , 29 , 30 ]. Our results showed that monosaccharides are the predominant soluble carbohydrates in fruit, with glucose as the major component, and were in accordance with previous findings for “Čačanska Lepotica” [ 9 , 27 , 28 ] and other cultivars of Prunus domestica [ 2 , 6 , 9 , 19 , 27 , 29 ]. It is worth mentioning that the contents of sucrose, glucose, fructose, and sorbitol differed from those published recently for the plum cultivar “Čačanska Lepotica” collected from the same place [ 13 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The higher TSC of the fruits collected in 2021 could be explained by the maturity stage and/or annual weather conditions [ 6 , 29 , 30 ]. Our results showed that monosaccharides are the predominant soluble carbohydrates in fruit, with glucose as the major component, and were in accordance with previous findings for “Čačanska Lepotica” [ 9 , 27 , 28 ] and other cultivars of Prunus domestica [ 2 , 6 , 9 , 19 , 27 , 29 ]. It is worth mentioning that the contents of sucrose, glucose, fructose, and sorbitol differed from those published recently for the plum cultivar “Čačanska Lepotica” collected from the same place [ 13 ].…”
Section: Resultssupporting
confidence: 93%
“…The fruits grown on “GXN-15” and “Janka” rootstock were the richest in malic and quinic acids, respectively, while the skins from the fruit grafted on “Wavit” rootstock contained the highest amount of both organic acids. The content of malic acid was nearly 2.5 (on average) times higher than that of quinic acid and was in accordance with previous studies of plum cultivars [ 6 , 13 , 19 ]. The amount of quinic acid was similar to that found for the plum cultivar “Čačanska Lepotica” collected from the same place [ 13 ], while that of malic acid was nearly two times higher.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Total polyphenol content (TPC) of the BSG extract and the freeze-dried digested samples (1 mg) was determined using a Folin–Ciocalteu method (colorimetric assay), with slight modifications [ 28 ]. A 10 µL aliquot of one of the sample solutions, namely the BSG extract, digested BSG extract (50 mg/mL), and gallic acid standard solutions (at concentrations ranging from 200 to 1000 µg/mL), was added to 50 µL of Folin–Ciocalteu reagent.…”
Section: Methodsmentioning
confidence: 99%